The influence of big five personality towards employee's performance at UiTM Pahang (Jengka Campus) / Nurlela Nasir - Nasir, Nurlela (Faculty of Business and Management, 2018)
Personality is one of the factors in determining to analyse the attitude as consistent thoughts and behaviour of an individual's that are stable over time and relatively consistent across different situation. Performance assesses whether a person performs a job well. Performance is an important criterion for organizational outcomes and success also describes as an individual-level variable or something a single person does. These two variables can give impact to the organization. This research was conducted to analyse the relationship between personality and employee's performance among the employees in Universiti Teknologi MARA (UiTM) Pahang, Jengka Campus. The researcher used descriptive statistic method to get the data that are collected through the questionnaire by gaining the feedback from the respondents. The questionnaires were divided into three section that comprised of Demographic, Personality and Employee's Performance. The questionnaire was distributed of 140 set but only 110 sets that researcher gets the feedback from the respondents. Based on this study, it can be concluding that there is the relationship between all of the personality trait and employee's performance. However, the only one result in the highest significant which are a very strong relationship and one of the variables get the moderate result as the lowest ranked between others variables. Besides, at the end of the report, there are some recommendations that are suggested by the researcher and conclusion on the overall analysis.